2019
DOI: 10.1038/s41420-019-0150-1
|View full text |Cite
|
Sign up to set email alerts
|

MEK5/ERK5 activation regulates colon cancer stem-like cell properties

Abstract: Colon cancer has been proposed to be sustained by a small subpopulation of stem-like cells with unique properties allowing them to survive conventional therapies and drive tumor recurrence. Identification of targetable signaling pathways contributing to malignant stem-like cell maintenance may therefore translate into new therapeutic strategies to overcome drug resistance. Here we demonstrated that MEK5/ERK5 signaling activation is associated with stem-like malignant phenotypes. Conversely, using a panel of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 78 publications
1
22
0
Order By: Relevance
“…First, the significant reduction in NF- κ B and P-NF- κ B expression in LPS-stimulated cells occurred after treatment with 100 μ g/ml of the extract. Pereira and colleagues showed that inhibiting ERK5 suppresses the NF- κ B signaling pathway [ 51 ]. Another study by Kloster et al reported that MEK signaling is important for activating NF- κ B signaling [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the significant reduction in NF- κ B and P-NF- κ B expression in LPS-stimulated cells occurred after treatment with 100 μ g/ml of the extract. Pereira and colleagues showed that inhibiting ERK5 suppresses the NF- κ B signaling pathway [ 51 ]. Another study by Kloster et al reported that MEK signaling is important for activating NF- κ B signaling [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also have been demonstrated that c‐Myc can be regulated at the transcriptional level by active ERK5. Pharmacologic inhibition or siRNA silencing of ERK5 down‐regulates gene and protein expression of c‐Myc in different settings 18,31‐34 . In the present study, the pharmacologic inhibition of both ERK5 and MEK5 suppressed c‐Myc expression in macrophages upon exposure to IL‐4.…”
Section: Discussionmentioning
confidence: 46%
“…Pharmacologic inhibition or siRNA silencing of ERK5 down-regulates gene and protein expression of c-Myc in different settings. 18,[31][32][33][34] In the present study, the pharmacologic inhibition of both ERK5 and MEK5 sup- and then stimulated with IL-4 for 48 h. Arginase-1-YFP (Arg1-YFP + ) expression was assessed by flow cytometry. Data are shown as mean ± SEM (n = 4) and are representative from two independent experiments.…”
Section: Discussionmentioning
confidence: 99%
“… 23 For example, inhibition of extracellular signal-regulated kinase 5 could eliminate cancer stem cells, thus improving colon cancer treatment. 24 Recently, through regulation of pathways involved in colon cancer stem cell, miRNAs have been reported to provide perspective on metastasis and recurrence of colon cancer. 25 Here, our results demonstrated that miR-377 could regulate cancer stem cell phenotypes, and inhibited EMT of colon cancer, suggesting that miR-377 had tumor suppressive ability against colon cancer via suppression of colon cancer stem cells and metastasis.…”
Section: Discussionmentioning
confidence: 99%